Developing mathematics teaching through inquiry: a response to Skovsmose and Säljö - Jaworski, Barbara; Fuglestad, Anne Berit (NOMAD Nordic Studies in Mathematics Education, 2010)
This paper constitutes a response to the article by Skovsmose and Säljö (2008) in Nomad. We focus on the concept of inquiry as used in the KUL projects at the University of Agder, Norway, 2004–2007, from which Skovsmose and Säljö offered an evaluation and critique. We begin by clarifying certain aspects of the two KUL projects, Learning communities in mathematics and ICT in mathematics learning. In doing so, we agree substantially with several of the points made by Skovsmose and Säljö. We go on to address their two main criticisms: that research in the KUL projects shows little documentation of inquiry processes or patterns of classroom interaction between teachers and students, or among students; and that the KUL projects demonstrate few attempts to use real life environments as a basis for establishing inquiry processes. Finally we come back to significant issues related to inquiry and the main focus of the two projects, further research questions and relations between the micro and the macro in mathematics education research.